Optimization of Hand Sanitizer Formulation with the Addition of Lemongrass (Cymbopogon citratus (DC.) Stapf) Essential Oil and a Combination of Essential Oils of Local Indonesian Empon-empon - Ariani, Sri Retno Dwi; Van Hayus, Elfi Susanti; Mulyani, Sri; Utomo, Suryadi Budi; Wathon, Muhammad Hizbul; Bilhaq, Natiq; Pramesti, Anastasia Diaz (Molekul, 2024)
ABSTRACT: This research aimed to optimize the formulation of hand sanitizer by incorporating lemongrass (Cymbopogon citratus (DC.) Stapf) essential oil in combination with essential oils of local Indonesian empon-empon: temu giring (Curcuma heyneana Val. & van Zipj.), temu kunci (Kaempferia pandurata Roxb.), and temu mangga (Curcuma amada Roxb.). The optimization of hand sanitizer formulation was done based on several tests. The first was organoleptic test by observing the aroma, color, and form; the second was pH, homogeneity, and spreadability testing, and; the third was testing the antibacterial activities of each hand sanitizer formula against Escherichia coli ATCC 25922 and Staphylococcus aureus ATCC 25922. The research stages encompassed isolation of essential oils, formulation and evaluation of hand sanitizers, antibacterial activities test, optimization of hand sanitizer formulation, and identification of the chemical compounds in the hand sanitizer with the optimum formulation using the GC-MS method. The study resulted in the hand sanitizer with the optimum formulation containing the essential oils of lemongrass (3%) and temu giring (3%), demonstrating very strong antibacterial bioactivities against both E. coli ATCC 25922 and S. aureus ATCC 25923, with inhibition zones measuring 29.70 mm and 60.08 mm, respectively. This hand sanitizer had a distinctive aroma, combining the scents of lemongrass and temu giring. It was in liquid form, clear, and homogeneous, with pH and spreadibility values of 5.4 and 6.4 cm, respectively. The quality complied with SNI quality standards No. 06-2588. The primary active ingredients were E-citral (22.10%), Z-citral (17.88%), and 1,8-cineol (17.63%). Keywords: Essential oil, hand sanitizer, lemongrass, temu giring, temu kunci, temu mangga.